Paradise lost A novel of suspense - Jance, Judith A. (New York : William Morrow, 2001)
What begins as an innocent Girl Scout camping trip quickly turns to a dangerous game of cat-and-mouse when Sheriff Joanna Brady uncovers the body of a murdered woman in the woods.
Keywords: Brady, Joanna (Fictitious character) -- Fiction; Mothers and daughters -- Fiction; Policewomen -- Fiction; Sheriffs -- Fiction; Cochise County (Ariz.) -- Fiction; Arizona -- Fiction; Mystery fiction